Polynomial force approximations and multifrequency atomic force microscopy - Platz, Daniel; Forchheimer, Daniel; Tholén, Erik A.; Haviland, David B. (Beilstein Journal of Nanotechnology, 2013)
We present polynomial force reconstruction from experimental intermodulation atomic force microscopy (ImAFM) data. We study the tip–surface force during a slow surface approach and compare the results with amplitude-dependence force spectroscopy (ADFS). Based on polynomial force reconstruction we generate high-resolution surface-property maps of polymer blend samples. The polynomial method is described as a special example of a more general approximative force reconstruction, where the aim is to determine model parameters that best approximate the measured force spectrum. This approximative approach is not limited to spectral data, and we demonstrate how it can be adapted to a force quadrature picture.
Keywords: AFM; atomic force microscopy; force spectroscopy; multifrequency; intermodulation; polynomial

(untitled) - Ohnesorge, F.; Binnig, G. (Science, 1993)

(untitled) - Giessibl, F. J. (Science, 1995)

(untitled) - Fukuma, T.; Kobayashi, K.; Matsushige, K.; Yamada, H. (Appl. Phys. Lett., 2005)

(untitled) - Gan, Y. (Surf. Sci. Rep., 2009)

(untitled) - Dürig, U. (Appl. Phys. Lett., 2000)

(untitled) - Sader, J. E.; Uchihashi, T.; Higgins, M. J.; Farrell, A.; Nakayama, Y.; Jarvis, S. P. (Nanotechnology, 2005)

(untitled) - Hölscher, H. (Appl. Phys. Lett., 2006)

(untitled) - Lee, M.; Jhe, W. (Phys. Rev. Lett., 2006)

(untitled) - Hu, S.; Raman, A. (Nanotechnology, 2008)

(untitled) - Katan, A. J.; van Es, M. H.; Oosterkamp, T. H. (Nanotechnology, 2009)

(untitled) - García, R.; Herruzo, E. T. (Nat. Nanotechnol., 2012)

(untitled) - Dürig, U. (New J. Phys., 2000)

(untitled) - Stark, M.; Stark, R. W.; Heckl, W. M.; Guckenberger, R. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Legleiter, J.; Park, M.; Cusick, B.; Kowalewski, T. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Sahin, O.; Magonov, S.; Su, C.; Quate, C. F.; Solgaard, O. (Nat. Nanotechnol., 2007)

(untitled) - Forchheimer, D.; Platz, D.; Tholén, E. A.; Haviland, D. B. (Phys. Rev. B, 2012)

(untitled) - Hutter, C.; Platz, D.; Tholén, E. A.; Hansson, T. H.; Haviland, D. B. (Phys. Rev. Lett., 2010)

(untitled) - Raman, A.; Trigueros, S.; Cartagena, A.; Stevenson, A. P. Z.; Susilo, M.; Nauman, E.; Contera, S. A. (Nat. Nanotechnol., 2011)

(untitled) - Platz, D.; Forchheimer, D.; Tholén, E. A.; Haviland, D. B. (Nanotechnology, 2012)

(untitled) - Platz, D.; Forchheimer, D.; Tholén, E. A.; Haviland, D. B. (Nat. Commun., 2013)

(untitled) - Platz, D.; Forchheimer, D.; Tholén, E. A.; Haviland, D. B. (Beilstein J. Nanotechnol., 2013)

(untitled) - Rodríguez, T. R.; García, R. (Appl. Phys. Lett., 2002)

(untitled) - Melcher, J.; Hu, S.; Raman, A. (Appl. Phys. Lett., 2007)

(untitled) - Platz, D.; Tholén, E. A.; Pesen, D.; Haviland, D. B. (Appl. Phys. Lett., 2008)

(untitled) - Platz, D.; Tholén, E. A.; Hutter, C.; von Bieren, A. C.; Haviland, D. B. (Ultramicroscopy, 2010)

(untitled) - Derjaguin, B. V.; Muller, V. M.; Toporov, Yu. P. (J. Colloid Interface Sci., 1975)

(untitled) - Luan, B.; Robbins, M. O. (Nature, 2005)

Polymer Handbook - Brandrup, J.; Immergut, E. H.; Grulke, E. A.; Abe, A.; Bloch, D. R. (Wiley & Sons, 2005)

(untitled) - Sahin, O.; Erina, N. (Nanotechnology, 2008)

(untitled) - Higgins, M. J.; Proksch, R.; Sader, J. E.; Polcik, M.; Mc Endoo, S.; Cleveland, J. P.; Jarvis, S. P. (Rev. Sci. Instrum., 2006)

(untitled) - Tholén, E. A.; Platz, D.; Forchheimer, D.; Schuler, V.; Tholén, M. O.; Hutter, C.; Haviland, D. B. (Rev. Sci. Instrum., 2011)